Uji Aktivitas Antibakteri Ekstrak Etanol 96% Daun Angsana (Pterocarpus Indicus) Dengan Konsentrasi 5% dan 10% terhadap Bakteri Shigella Dysenteriae - Wulan Pratiwi; Putri Nur Riani; Melly Annisa Putri; Nazwa Vidya Malik (Jurnal Kridatama Sains dan Teknologi, 2026)
Diarrhea is an abnormal condition of fecal excretion commonly caused by bacterial, viral, or parasitic infections, as well as poor sanitation and hygiene. One of the main pathogenic bacteria responsible for diarrhea, particularly bacillary dysentery, is Shigella dysenteriae. The high incidence of diarrhea has encouraged the search for alternative treatments derived from natural materials, including angsana leaves (Pterocarpus indicus), which are known to contain bioactive compounds. This study aimed to determine the antibacterial activity of ethanolic extract of angsana leaves against the growth of Shigella dysenteriae at concentrations of 5% and 10%. The research employed a Completely Randomized Design (CRD) with a post-test only control group design. The samples consisted of six treatment groups with four replications each. Angsana leaf extract was obtained through an extraction process using 96% ethanol and subsequently tested for antibacterial activity using the disc diffusion method. All treatments were incubated for 24 hours to observe the formation of inhibition zones. The results showed that no inhibition zones were formed in the negative control group or in the groups treated with angsana leaf extract at concentrations of 5% and 10%, indicating the absence of antibacterial activity against Shigella dysenteriae. Normality testing revealed that the data were not normally distributed. Based on these findings, it can be concluded that the ethanolic extract of angsana leaves (Pterocarpus indicus) at concentrations of 5% and 10% is not effective as an antibacterial agent against Shigella dysenteriae. Further studies using higher extract concentrations or different extraction methods are recommended to obtain more optimal results.